Microtus agrestis - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Microtus agrestis (Linnaeus, 1761). Fauna Suec., 11(2):11. TYPE LOCALITY: Sweden, Uppsala. DISTRIBUTION: Britain, Scandinavia, and France east through Europe and Siberia to Lena River; south to Pyrennes, N. Portugal, N. Yugoslavia, Altai Mtns., Sinkiang (China) (SW), and Lake Baikal. COMMENT: Subgenus Microtus; see Anderson, 1959, Univ. Kans. Publ. Mus. Nat. Hist., 9:496 (Arvalomys of Chaline, 1974:440-450). Sometimes regarded as conspecific with pennsylvanicus, as by Klimkiewicz, 1970, Mammalia, 34:641-665, but not closely related; see Frank, 1959, Z. Saugetierk., 24:91-93, and Vorontsov and Lyapunova, 1976, in Kontrimavichus, ed., [Beringia in Cenozoic], Acad. Sci. Vladivostok. ISIS NUMBER: 5301410008080001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 490, DOI: 10.5281/zenodo.7353034